Study of variation in price of various antidiabetic drugs available in Indian market - Date, Amit Padmakar; Mahajan, Harshal M.; Dashputra, Amruta V.; Bhosale, Rahul R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes mellitus in early age is on the alarming rise in India, requiring lifelong treatment. There is a wide range of variation in the prices of antidiabetic drugs marketed in India. Hence, we decided to study price variations in the oral antidiabetic drugs available, either singly or in combination, and number of manufacturing companies for each, and to evaluate the difference in cost of different brands of same active drug by calculating percentage variation of cost. Methods: Cost of a particular drug being manufactured by different companies, in the same strength and dosage forms was obtained from “Current Index of Medical Specialties” July-October 2014 and “Indian Drug Review” July 2014. The difference in the maximum and minimum price of the same drug, manufactured by different pharmaceutical companies and percentage variation in price was calculated. Results: Percentage price variation among different group of drugs was found to be as follows: in sulfonylureas, it was highest in glimepiride 2 mg 836.44%, among biguanides - metformin 500 mg 245.55%, among thiazolidionediones-pioglitazone 15 mg 600%, among α glucosidase inhibitors - voglibose 284.61% and meglitinides - repaglinide 0.5 mg 181.40%. Among combination therapy glimepiride 1 mg + metformin 500 mg 366.66%, pioglitazone + metformin 207.51%, pioglitazone + glimepiride 268.42% showed maximum variation in price. Conclusion: The average percentage price variation of different brands of the same oral antidiabetic drug manufactured in India is very wide. The appropriate changes in the government policy, sensitizing the prescribers about cost of therapy and proper management of marketing drugs should be directed toward maximizing the benefits of therapy and minimizing negative economic consequences.